2018
DOI: 10.1109/tii.2018.2811734
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the Potential Economic Benefits of Flexible Industrial Demand in the European Power System

Abstract: The envisaged decarbonization of the European power system introduces complex techno-economic challenges to its operation and development. Demand flexibility can significantly contribute in addressing these challenges and enable a cost-effective transition to the low-carbon future. Although extensive previous work has analyzed the impacts of residential and commercial demand flexibility, the respective potential of the industrial sector has not yet been thoroughly investigated despite its large size. This pape… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 25 publications
0
15
0
Order By: Relevance
“…Industrial and commercial demand side response (I&C DSR) is highly dependant on specific business cases and requires detailed modelling of technological processes [33]. For example, in [34] Oikonomou and Parvania perform comprehensive modelling of a water desalination plant to determine potential capacity and marginal cost for providing DSR.…”
Section: Iandc Dsrmentioning
confidence: 99%
“…Industrial and commercial demand side response (I&C DSR) is highly dependant on specific business cases and requires detailed modelling of technological processes [33]. For example, in [34] Oikonomou and Parvania perform comprehensive modelling of a water desalination plant to determine potential capacity and marginal cost for providing DSR.…”
Section: Iandc Dsrmentioning
confidence: 99%
“…In this setting, flexible demand technologies, enabling temporal redistribution (shifting) of electricity demand in time, have attracted great interest, since they exhibit the potential to support system balancing and reduce peak demand levels. Numerous studies have investigated these beneficial impacts of demand flexibility on electricity systems' short-term operation and long-term development [2][3][4][5][6].…”
Section: Background and Motivationmentioning
confidence: 99%
“…Large consumers already have the possibility to make the flexibility in their demand available to the system operator [4], but incentives for smaller consumers to actively use the flexibility in their demand are currently not widespread. Nevertheless, surveys have shown that smaller consumers are willing to actively participate in demand-side management and have part of their load being shed or deferred if they are appropriately compensated [5].…”
Section: Introductionmentioning
confidence: 99%